THE METHOD OF PART MIDDLING IN THE INTEGRAL- DIFFERENTIAL SYSTEMS WITH DOUBLE IMPULSIVE ACTION - Гулька, Степан Степанович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The method of middling by Crilov-Bogolubov-Mitropopolsky is applied to the systems of integral-differential equalizations with double impulsive action.